Is cognitive behavior therapy effective in treatment of game addiction among indonesian adolescents during covid-19 outbreak? - Amalianita, Berru; Putri, Yola Eka; Fadli, Rima Pratiwi; Fitria, Linda; Ifdil, Ifdil (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
The purpose of this article is to investigate the efficacy of cognitive behavior therapy (CBT) in treating gaming addiction among Indonesian teenagers during the covid-19 epidemic. In this context, teenagers. By a comprehensive review of the literature, we examine the existing data on the efficacy of CBT in treating gaming addiction among Indonesian adolescents, in terms of the problem's evolution before and after the covid-19 epidemic. During the covid-19 epidemic, our study will expose the present situation of gaming addiction among Indonesian teenagers and investigate the efficacy of CBT in treating it. In addition, this work will be valuable for shedding light on future research in this field.